Good time [videorecording (DVD)] - Safdie, Josh; Safdie, Benny; Pattinson, Robert, 1986-; Leigh, Jennifer Jason, 1962- (Lions Gate Entertainment, 2017)
After a botched bank robbery lands his younger brother in prison, Constantine Nikas embarks on a twisted odyssey through New York City's underworld in an increasingly desperate, and dangerous attempt to get his brother out of jail. Over the course of one adrenalized night Constantine finds himself on a mad descent into violence and mayhem as he races against the clock to save his brother and himself, knowing their lives hang in the balance.